2022
DOI: 10.4081/jphia.2022.2408
|View full text |Cite
|
Sign up to set email alerts
|

Determination of factors affecting post-partum depression in primary healthcare during the COVID-19 pandemic

Abstract: Postpartum depression is a phenomenon that occurs in the first postpartum days. Symptoms of postpartum depression peak on days 3 to 5 postpartum with a duration ranging from a few hours to several days. Of course, this will be different during the Covid-19 pandemic. The aim of this study was to analyze the determinants that influence the incidence of post-partum depression in primary health during the pandemic. The method in this research is descriptive analysis with cross sectional approach with a total sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For instance, Nurbaeti et al (2019) found that 19.88% of postpartum mothers in South Jakarta, Indonesia, experienced depressive symptoms following childbirth. More recently, a study by Solikhah et al (2022) found that 57% of mothers experienced PPD in Malang, East Java, Indonesia. In the general population, Sarfika et al ( 2021) found higher about 71.70% of the population in Indonesia with depressive symptomatology during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Nurbaeti et al (2019) found that 19.88% of postpartum mothers in South Jakarta, Indonesia, experienced depressive symptoms following childbirth. More recently, a study by Solikhah et al (2022) found that 57% of mothers experienced PPD in Malang, East Java, Indonesia. In the general population, Sarfika et al ( 2021) found higher about 71.70% of the population in Indonesia with depressive symptomatology during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on PPD were conducted in various countries during the COVID-19 pandemic (Safi-Keykaleh et al, 2022;Shuman et al, 2022;Usmani et al, 2021). Meanwhile in Indonesia, Solikhah et al (2022) found that the determinant factor of PPD during the COVID-19 was first-time mothers and attitudes. At the same time, other factors have not been documented.…”
mentioning
confidence: 99%
“…4 Postpartum period is recognized as a transitional phase in a woman's life when she assumes the role of a mother, significantly impacting her emotions. 5 During this period, there are changes in various aspects such as role, responsibility, identity, physicality, and social dynamics. [6][7] The fluctuations in steroid hormone levels play a crucial role in emotion processing, affecting reactivity within a network that includes the amygdala, insula, anterior cingulate cortex, and the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…11 These factors contribute to a mother's susceptibility to psychological breakdown. 5 Postpartum encompasses various psychological breakdowns, including postpartum blues, baby blues, postpartum depression, and postpartum psychosis. 13,14 The International Statistical Classification of Diseases (ICD-10) defines postpartum depression as a mental and behavioral disorder.…”
Section: Introductionmentioning
confidence: 99%